Reconceptualising loss in retailing: calling time on 'shrinkage'. Issue 4 (8th August 2017) - Beck, Adrian
Abstract: For more than 100 years the retail industry has relied primarily upon the term 'shrinkage' to define how retail 'losses' are understood and controlled. There is, however, little consensus on what types of loss should be included and excluded when this term is used, making most benchmarking exercises difficult to perform with any degree of accuracy. In addition, as retailing becomes ever more complex and demanding, and a greater range of data sources become available, the traditional approaches to understanding and measuring loss in retailing seem increasingly anachronistic. Based upon extensive interviews and focus group discussions with senior retail executives from Europe and the U.S., this article puts forward a framework for developing a more inclusive and broad ranging definition and typology of retail losses, using the umbrella term Total Retail Loss.